“Is The Banking Industry The Right Choice To Invest?” (Analisis Laporan Keuangan PT. Bank Central Asia, PT. Bank Rakyat Indonesia, PT. Bank Nasional Indonesia, PT. May Bank dan PT. Bank Permata Periode 2013-2017) - Silmi Silmi; Kevry Ramdany; Yudi Mufti Prawira (Universitas Batanghari Jambi, 2020)
Financial statements are one of the analytical tools that contain information that can be used by potential investors to make investment decisions. Prospective investors need a capable and trusted analysis to analyze the financial statements of the industry in the Bank, to determine which banks need funds for short-term investors and long-term prospective investors involve investing their capital through the purchase of shares, explained to the Bank that provides funds as expected investment returns by potential investors even more. There are 5 banks that submit comparisons and assess their ratios and performance in this study so that potential investors can invest appropriately, expecting: PT. Bank Central Asia, PT. Bank Rakyat Indonesia, PT. Bank Nasional Indonesia, PT. May Bank and PT. Bank Permata, for 5 years analysis time period. From the results of research and analysis conducted, Bank BCA is the right choice for investors for short-term investors and BRI is the right choice for potential investors for long-term investment.